Prediction and Diagnosis of Post Transplant Diabetes - J. Yates, Christopher; J. Cohney, Solomon (Current Diabetes Reviews, 2015)
The identification of at-risk individuals prior to transplantation may enable implementation of measures to prevent or delay PTDM development, while early detection facilitates prompt management and may prevent acute and chronic complications. Thus, in this review, we examine proposed tools for the prediction of PTDM for use prior to and following solid organ transplantation. This includes PTDM prediction models based on biochemical assessments of glycaemia and other indices, in addition to those solely based on clinical parameters. We also examine the available methods for diagnosis of PTDM early and late post-transplant, including the advantages and limitations of fasting plasma glucose (FPG), OGTT, random plasma glucose and HbA1c assessment. Key findings are that OGTT should remain the gold standard diagnostic method for PTDM, however, there is emerging data to support a role for HbA1c beyond 3 months posttransplant. FPG has low sensitivity during the first year post-transplant. Improved prediction and diagnosis of PTDM may lead to improvements in patient survival, quality of life and health care costs in future.
Keywords: PTDM